2006
DOI: 10.1002/mus.20697
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic laryngeal muscles are spared from myonecrosis in the mdx mouse model of Duchenne muscular dystrophy

Abstract: Intrinsic laryngeal muscles share many anatomical and physiological properties with extraocular muscles, which are unaffected in both Duchenne muscular dystrophy and mdx mice. We hypothesized that intrinsic laryngeal muscles are spared from myonecrosis in mdx mice and may serve as an additional tool to understand the mechanisms of muscle sparing in dystrophinopathy. Intrinsic laryngeal muscles and tibialis anterior (TA) muscle of adult and aged mdx and control C57Bl/10 mice were investigated. The percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
59
1
12

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 24 publications
7
59
1
12
Order By: Relevance
“…19,46 We have previously reported that the ILM of mdx mice are spared from degeneration despite the lack of dystrophin. 30 In this study we observed that expression of the key calcium-regulatory proteins SERCA1 and calsequestrin is increased in dystrophic ILM. This supports the hypothesis that these muscles may have a better ability to maintain calcium homeostasis, which is correlated with muscle sparing.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…19,46 We have previously reported that the ILM of mdx mice are spared from degeneration despite the lack of dystrophin. 30 In this study we observed that expression of the key calcium-regulatory proteins SERCA1 and calsequestrin is increased in dystrophic ILM. This supports the hypothesis that these muscles may have a better ability to maintain calcium homeostasis, which is correlated with muscle sparing.…”
Section: Discussionmentioning
confidence: 86%
“…1 We have demonstrated that intrinsic laryngeal muscles (ILM) are protected against myonecrosis in mdx mice. 30 Dystrophic extraocular muscles (EOM) are also spared in DMD, 2,27,31,36 possibly because of a greater ability to maintain calcium homeostasis compared with other striated muscles. 27 Other factors seem to be involved in EOM protection as well.…”
mentioning
confidence: 99%
“…However, our analysis did not include different segments of the nerve and axonal degeneration might be too fast to be detected at a given time point. Nevertheless, other factors may be involved in the remodeling of the human larynx such as sprouting and retraction of nerve terminals, which may occur at the neuromuscular junction in response to the laryngeal muscle fiber regeneration normally seen in aged humans (Malmgren et al, 2000) and mice (Marques et al, 2007). The synaptic rearrangement that is known to occur in old neuromuscular junctions may affect the number of MUs estimated by clinical methods (Gambino et al, 1990), but not by morphological methods because it does not necessarily involve axon loss.…”
Section: Discussionmentioning
confidence: 98%
“…However, not all subtypes of skeletal muscles are affected in the same way in x-linked muscular dystrophy. For example, intrinsic laryngeal and certain distal muscle fibers, as well as extraocular muscle (EOM), are protected from a severely degenerative phenotype in dystrophic organisms [5][6][7][8][9][10][11]. Although the contractile efficiency of EOM is weakened in various muscle-related pathologies, such as myasthenia gravis, myasthenic syndromes, botulism, and myotonia congenita [12][13][14], they are usually spared in DMD patients [15][16][17].…”
Section: Introductionmentioning
confidence: 99%